Combining Biosafety Experts’ Evaluations and Workers’ Perceptions to Disclose Biological Risks in Biomedical Laboratories - Dionysios Vourtsis; Efstathia Papageorgiou; Anastasios Kriebardis; George Albert Karikas; Gijsbert van Willigen; Kostas Kotrokois; Georgios Dounias; Petros Karkalousos (European Scientific Journal, ESJ, 2025)
Objectives: This paper focuses on examining the biological risks in biomedical laboratories of public hospitals in Athens, Greece, by combining expert evaluations and laboratory workers’ perception. It also aimed to review how personnel managed biological materials, assess the level of safety awareness and training of workers, and propose hazards mitigation actions according to local legislation and international biosafety guidelines. Materials and Methods: A total of 36 biosafety level 2 (BSL-2) laboratories in 20 hospitals were evaluated for biosafety containment specifications and adherence to biosafety procedures. The study was conducted as a cross-sectional survey using a checklist and a detailed health and safety (H&S) questionnaire, focusing on biosafety and biorisk management. An expert biosafety officer inspected and completed a checklist for each laboratory (n=36) across the 20 hospitals. Additionally, 415 lab professionals completed a biosafety-specific health and safety questionnaire. Results: Both the checklists and questionnaires revealed that, although some positive findings were observed, a significant percentage of laboratories lacked effective management of biological agents and materials overall. The main deficiencies identified included restricted access, safety equipment, standard operating procedures (SOPs), biorisk management systems, risk assessments, biosafety manuals, biosafety officers, accident reporting, and biosafety training programs. Conclusion: The significant shortcomings in some areas of engineering and administrative controls, as well as in the implementation of Greek and European biosafety legislation, demonstrate that the laboratories do not fully comply with  internationally accepted BSL-2 standards. Therefore, there is an urgent need for more comprehensive and proactive measures, adequate biosafety training for workers, and stricter enforcement of existing laws and directives to ensure the safety of laboratory professionals, the community, and the environment.